UV-vis investigation of (CTC/Orthodox/Green) tea in presence of Brij 35/Water system - Bhattarai, Ajaya; Mitruka, Jay Narayan; Chapagain, Subas Kumar; Shrestha, Prem Kumar (BIBECHANA, 2014)
The precise measurements of (CTC/Orthodox/Green) Tea absorbance in presence of Brij 35/Water system at room temperature by UV-vis technique are reported. The concentrations of Brij 35 [Polyoxyethylene lauryl ether] were varied from 0.01 to 0.02 mol/lt. Tea concentration in quvette during UV-vis spectrum registration was the same. Obtained results showed a noticeable decreasing of Tea absorbance as a function of Brij 35 concentration. There is evidence of Tea absorbance in the following order: Orthodox > CTC >Green. DOI: http://dx.doi.org/10.3126/bibechana.v11i0.10378 BIBECHANA 11(1) (2014) 40-45